Adaptive etalon suppression technique for long‐term stability improvement in high index contrast waveguide‐based laser absorption spectrometers. Issue 15 (1st July 2019) - Zhang, E.J.; Tombez, L.; Teng, C.C.; Wysocki, G.; Green, W.M.J.
Abstract : The authors present an adaptive algorithm based on a non‐linear regression model for mitigating time‐varying etalon drifts in line‐scanned optical absorption spectrometers. By dynamically varying the etalon spectral background using physically realistic degrees of freedom, the authors' dynamic etalon fitting‐routine (DEF‐R) significantly increases the spectral baseline recalibration interval as compared to conventional fringe subtraction models. They provide an empirical demonstration of the efficacy of DEF‐R using an on‐chip 10 cm silicon waveguide for near‐infrared methane absorption spectroscopy at 6057 cm −1, which suffers significant etalon spectral noise due to reflections and multi‐path interference from stochastic line‐edge roughness imperfections. They demonstrate the corresponding improvement in both spectral clean‐up and long‐term stability via Allan‐variance analysis. For the sensor presented here, application of DEF‐R enables Gaussian‐noise limited performance for more than 10 2 s and provides almost an order‐of‐magnitude improvement in stability time with respect to conventional baseline subtraction. Although DEF‐R is applied here to an on‐chip sensor embodiment, they envision their technique to be applicable to any absorption sensor limited by time‐varying etalon drifts.